Impact of a 6-month treatment with intragastric balloon on body composition and psychopathological profile in obese individuals with metabolic syndrome. Issue 1 (December 2016) - Guedes, Erika; Madeira, Eduardo; Mafort, Thiago; Madeira, Miguel; Moreira, Rodrigo; Mendonça, Laura; Godoy-Matos, Amélio; Lopes, Agnaldo; Farias, Maria
Abstract Background The aim of this study was to investigate the effects of a 6-month treatment with intragastric balloon (IGB) on body composition and depressive/anxiety symptoms in obese individuals with metabolic syndrome (MS). Methods Fifty patients (aged 18–50 years) with obesity and MS were selected for treatment with IGB for 6 months. Body composition was verified with dual-energy X-ray absorptiometry (DXA) at baseline and right after IGB removal. Anxiety/depressive symptoms were assessed with the Beck Depression Inventory (BDI) and the hospital anxiety and depression scale (HADS) at baseline and after 6 months of treatment. Results In total, 39 patients completed the study. After 6 months, there were significant decreases in weight (11.7 ± 9.6 kg, p < 0.0001) and waist circumference (9.3 ± 8.2 cm, p < 0.0001). Weight loss was also demonstrated by DXA and corresponded to decreases of 3.0 ± 3.4% in body fat percentage, 7.53 ± 7.62 kg in total body fat, and 3.70 ± 4.89 kg in lean body mass (p < 0.001 for all comparisons). Depressive symptoms scores decreased by a mean of 4.57 ± 10.6 points when assessed with the BDI (p = 0.002) and 1.82 ± 5.16 points when assessed with the HADS-Depression (p = 0.0345). Anxiety symptoms scores decreased by a mean of 1.84 ± 4.04 points when determined with the HADS-anxiety (p = 0.0066). The decrease in body fat percentage was the parameter that best correlated with improvements in depressive (p = 0.008) and anxiety symptoms (p = 0.014). Conclusions In obese individuals with MS, fat mass reduction was associated with short-term improvements in depressive and anxiety symptoms. Trial Registration Registered at ClinicalTrials.gov, NCT01598233